Application of prospect theory on travel choice behavior prediction - Lin, Tinglong. (2012)
Travel behavior has always been an important concern for transport researchers and transport services providers. It consists of many processes of decision making with applications of various disciplines such as economics, social sciences, statistics and psychology. The study focuses on the application of Prospect Theory in predicting travel decisions in uncertainty.From the various research articles and journals, it can be seen that currently, the most widely used and accepted model for travel choice behavior prediction is based on the Expected Utility Theory. However, there have been increasing criticisms on the application of Expected Utility Theory on transport choice behavior as the model is a normative model that is concerned with the question “what decision people should make”, assuming complete rationality of individual. But for transportation research, a descriptive model is more relevant as it is concern with people’s decision making as it is, not as it should be. Also, the models based on Expected Utility Theory did not take fully into account the uncertainty of traveling and there are differences in choice behavior between risky and riskless choice.